PARTICIPATORY EDUCATION IN PREVENTING DEVIANT BEHAVIOR IN ELEMENTARY SCHOOL STUDENTS IN MANADO CITY - Frelly Valentino Kuhon; Ronald Imanuel Ottay; Oksfriani Jufri Sumampouw; Jeini Ester Nelwan (International Journal of Multidisciplinary Reseach, 2026)
Deviant behavior among elementary school students remains a critical issue in basic education because it can disrupt the learning process and hinder character formation and children's psychosocial well-being. At this stage, students are increasingly exposed to broader environmental influences, including peers, digital media, and family dynamics, which have the potential to trigger behaviors such as dishonesty, bullying, and rule-breaking. This community service activity aims to increase students' understanding of the forms, causes, and impacts of deviant behavior, while equipping them with practical strategies to prevent and address it. Furthermore, this activity also aims to encourage students' role as agents of positive change and strengthen collaboration between students, teachers, and parents in strengthening character education. The activity was held on August 29, 2025, at Kartika Jaya Elementary School XXI-1, Manado City, using an educational-participatory approach through interactive lectures, case study-based group discussions, simulations and role-playing, and reflection sessions. Evaluation was carried out through direct observation and responsive feedback from participants. The results of the activity showed an increase in students' understanding of deviant behavior and its causal factors, as well as an increase in their ability to implement prevention strategies, such as rejecting negative influences, reporting inappropriate behavior, and building positive social interactions. Students also demonstrated a commitment to implementing positive behavior in their daily lives, supported by active participation and positive responses from both students and teachers. It was concluded that a participatory and contextual educational approach was effective in raising awareness and shaping positive attitudes in elementary school students. Therefore, ongoing mentoring, strengthening the role of parents, and integrating character education into the school curriculum are recommended to ensure the sustainability of the activity's impact.